Signifikansi Maqashid al-Syariah dalam Pengembangan Ekonomi Syariah - Purkon, Arip (Penerbit Yayasan Daarul Huda Kruengmane, 2024)
Ushul fiqh is a method for establishing fiqh law. One of the approaches used in ushul fiqh is the maqashid al-syariah approach. The maqashid al-syariah approach is used to examine the meaning or purpose of establishing a law. In practice, maqashid al-syariah cannot be separated from the sharia text or nash itself. Maqashid al-syariah has quite a big role, especially in establishing laws that are not textually stated explicitly in the text or are still dzanni al-dilalah in nature. Many of the problems that arise in sharia economics today are not written textually in the texts of the Al-Quran and Sunnah, so the maqasid al-syariah approach becomes very relevant.